Resilience in the face of changing living conditions in Guangzhou, China – insights and perspectives from psychology - Bercht, Anna Lena (ERDKUNDE, 2013)
To respond to increasing intercity competition and to improve its leading role as the regional centre in southern China, the Guangzhou government has been constructing the “South Railway Station” in Shibi Village, the largest passenger railway station in Asia. This paper explores and reflects upon how the inhabitants of this village appraise and deal with the project’s impacts on their living conditions. In this regard, the question is particularly considered as to why some individuals show adaptive functioning in the face of significant risk or adversity while others do not. Which risk and protective factors play a role in modifying the quality of stress experience and interface with the phenomenon of individual resilience? The purpose of this article is twofold. Firstly, it aims to enrich the geographical discourse on vulnerability and resilience by taking a psychological perspective and presenting and applying aspects of the transactional stress model of LAZARUS and of current psychological research on individual resilience. Secondly, it seeks to analyze the effect of risk and protective factors especially in relation to complex person-environment relationships that seem neither amenable to modification nor controllable by “visible” action. Problem-based interviews (including narrative sequences) with Shibi’s inhabitants and auto-photography reveal that, in particular, intrapsychological problem- and emotion-focussed coping modes and person-related dispositions such as an internal locus of control or optimism contribute to features of individual resilience.